2006
DOI: 10.1001/archpsyc.63.2.130
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Depression, Mild Cognitive Impairment, and Cognitive Decline

Abstract: One of the most important recommendations to emerge from the meeting discussions is for increased collaboration among clinical and epidemiological investigators whose work focuses in the area of depression with those working primarily in the area of memory disorders. Directions for future research were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
217
2
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 242 publications
(233 citation statements)
references
References 136 publications
9
217
2
3
Order By: Relevance
“…The strengths of the present study were : the large sample size ; the long follow-up period of up to 10 years ; the high follow-up rate ; and the broad inclusion criteria for MCI in which mild depressive symptomatology was not excluded at baseline, in accordance with current recommendations (Steffens et al 2006). The limitations of the study were : the relatively small number of subjects with a 10-year follow-up, and the lack of pathological confirmation of the clinical diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strengths of the present study were : the large sample size ; the long follow-up period of up to 10 years ; the high follow-up rate ; and the broad inclusion criteria for MCI in which mild depressive symptomatology was not excluded at baseline, in accordance with current recommendations (Steffens et al 2006). The limitations of the study were : the relatively small number of subjects with a 10-year follow-up, and the lack of pathological confirmation of the clinical diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several hypotheses regarding the relationship between depression, MCI and AD (Steffens et al 2006 ;Wilson et al 2008). One hypothesis proposes that depressive symptoms contribute to the development of AD.…”
Section: Discussionmentioning
confidence: 99%
“…The quantitative measures included performance-based tasks similar to those that participants complete in their everyday activities. These measures are not only related to cognition, but also predict subsequent decline (Pérès et al 2008;Steffens et al 2006). The far transfer measures were categorized as self-report (qualitative) or performance-based (quantitative).…”
Section: Methodsmentioning
confidence: 99%
“…Studies of elderly depressed patients have repeatedly suggested a potential involvement of the prefrontal cortex and temporal lobe structures, such as the hippocampus, in the disorder (for review see Alexopoulos et al, 2005;Steffens et al, 2006). In a subset of elderly depressed patients with major depression, the first episode occurs late in life (Alexopoulos et al, 1988).…”
Section: Introductionmentioning
confidence: 99%